PENGARUH METODE NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR SEJARAHSISWA KELASA XI IPS SMA NEGERI 4 MUARO JAMBI - Dena Susmaya, Satriyo Pamungkas (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2017)
AbstracThe purpose of this research is to determine the effect of the method of Number Head Together on the learning outcomes of students of class XI IPS SMA Negeri 4 Muara Jambi. The research method used is experimental method. This experimental research involves two classes, the experimental class using the method of Number Head Together and control class using conventional methods. The result of the research, the average score for the experimental class is 75,36 with the standard deviation of 12,98 and the controlreat class is 66,67 and with standard deviation 15,28. And the results of the hypothesis test obtained t count = 6.99 and ttabel = 2.00 so it can be concluded that method number head together affect student learning outcomes, student learning outcomes that use method number head together better than the results of learning using conventional methods in the class XI IPS semester 1 SMA Negeri 4 Muaro jambiKeywords: Method, Number Head Together, Learning Outcomes